2014
DOI: 10.1007/s13277-014-2408-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of gelatin sponge microparticles in a rabbit VX2 liver tumor model of hepatic arterial chemoembolization

Abstract: The objective of this study is to investigate pharmacokinetics of gelatin sponge microparticles (GSMs) combined with epirubicin in a rabbit VX2 liver tumor model of hepatic arterial chemoembolization (TACE). Eighteen successful models of VX2 in New Zealand white rabbits was established, which were divided into three groups randomly: HAI group (n = 6), the epirubicin solution (epirubicin 10 mg mixed with saline 10 ml into the hepatic artery); GSMs-TACE group (n = 6), GSMs (20 mg) mixed with epirubicin solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…GSPs has the sustained effects of chemotherapy drugs, which make the less chemotherapy drugs maintain longer period of drug concentration, and this may be one of the reasons to achieve better efficacy in this study. [27] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GSPs has the sustained effects of chemotherapy drugs, which make the less chemotherapy drugs maintain longer period of drug concentration, and this may be one of the reasons to achieve better efficacy in this study. [27] …”
Section: Discussionmentioning
confidence: 99%
“…Secondly, our previous study had documented the significantly higher chemotherapeutic drug concentration in tumor tissue and lower chemotherapeutic drugs in peripheral plasma compared with intra-arterial infusion in the VX2 animals model treated with GSMs-TACE. [27] That may be one of therapeutic mechanisms of GSMs-TACE for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested the usage of GSMs-TACE comparing to c-TACE group and hepatic arterial infusion (HAI) group have higher concentration of chemotherapy drug with slow drug release. 31 Human research also showed good tolerance on GSMs and the OS rate was 100% in six months and 87.5%, in one year. 32 Other parallel studies confirmed the safety and effectiveness of gelatin sponge particle TACE for treatment of the Barcelona-Clinic Liver Cancer (BCLC) stage B HCC patients.…”
Section: Gelatin Sponge Particle Tacementioning
confidence: 90%
“…Drugs delivered directly by the microspheres increase tumor necrosis and response rate. [6,7] The domestically produced 350 to 560 μm GSPs used in this study have previously been used for regional embolization in the treatment of HCC. Treatment resulted in tumor necrosis and shrinking, rapid recovery of liver function, and good short-term effectiveness.…”
Section: Introductionmentioning
confidence: 99%